Combining extraction and cultivation methods for soil seed bank analysis increases number of captured species and their similarity to above-ground vegetation - Plohák, Petr; Švehláková, Hana; Stalmachová, Barbara; Goňo, Miroslava; Dvorský, Tomáš (Frontiers in Plant Science, 2025)
IntroductionAnalysis of aboveground vegetation and soil seed bank is an important source of data on the state and dynamics of vegetation. It is especially important in landscapes exposed to disturbances, which have lost their functions. For our research, a post-mining area in the region of the Upper Silesian Black Coal Basin was selected, whose relief and ecosystems are strongly disturbed by underground mining and are currently also affected by ongoing climate change.MethodData collection for our research took place in the territory of two waterlogged subsidence basins in the Karvina region, Czech Republic. We evaluated 30 phytosociological releves using techniques of Zurich – Montpellier school and 540 soil cores using cultivation and extraction method.ResultsIn the above-ground vegetation, 115 plant species were identified. By cultivating soil samples, we determined 60 species from 1,487 seedlings, by extraction method 66 species from 5,999 seeds. A statistically significant effect of the presence of the tree layer on the number of species obtained by the extraction method was demonstrated. There is also a statistically significant difference between the selected analysis methods in terms of the length of the captured seeds and their seed mass.DiscussionThe construction of a rarefaction curve demonstrated that the use of cultivation and extraction methods leads to a greater capture of soil seed bank species. The similarity between the species composition of aboveground vegetation and the soil seed bank correspond to similarities observed in other studies from degraded habitats. Very low similarity between the species of the soil seed bank from cultivation and extraction method is probably caused by the highly variable distribution of seeds in the soil in time and space.